Simultaneous Estimation of Nimesulide, Cetirizine Hydrochloride and Pseudoephedrine Hydrochloride in Combined Tablet Dosage Form Using RP-HPLC Method - K. Jain, Dinesh; Dubey, Nitin; Malav, Pramod (Asian Journal of Chemistry, 2012)
A simple, accurate and precise RP-HPLC method has been developed for the simultaneous estimation of nimesulide, cetirizine hydrochloride and pseudoephedrine hydrochloride in commercially available tablet formulations. The chromatographic separation was achieved on Luna C8 column using acetonitrile:phosphate buffer:triethyl amine (pH 6.5 ± 0.1) (50:50:0.1 % v/v/v) as mobile phase at a flow rate of 1.0 mL/min. Quantitation was carried out at lmax of 266, 230 and 256 nm for nimesulide, cetirizine hydrochloride and pseudoephedrine hydrochloride, respectively. The method was validated as per ICH guidelines. The method may be applied for the routine simultaneous estimation of the above mentioned drugs in tablet dosage form.